Effect of pioglitazone on in-stent restenosis after coronary drug-eluting stent implantation: a meta-analysis of randomized controlled trials. - Ming-duo Zhang; Yu-hui Zhang; En-jun Zhu; Shi-bin Qiao; Shu-zheng Lv; Quan-ming Zhao (PLoS ONE, 2014)
In-stent restenosis (ISR) remains a common life-threatening complication and some studies have shown that pioglitazone can reduce the incidence of ISR in patients with drug-eluting stents (DES) implantation. We conducted a meta-analysis to assess the effect of pioglitazone in preventing ISR after DES implantation.Randomized controlled trials (RCTs) investigating the effects of pioglitazone for ISR after DES implantation were identified by systematic searches of multiple online databases and manual searches of related reference lists of identified trials through May 2014. The primary endpoint was the rate of ISR. Secondary endpoints included minimum lumen diameter, percentage stenosis of stented vessels, late loss, in-stent neointimal volume, target vessel revascularization (TVR), target lesion revascularization, myocardial infarction, stent thrombosis and death.Five studies, comprising 255 pioglitazone-treated patients and 245 controls, were identified in the current meta-analysis. Pioglitazone did not significantly reduce the rate of ISR (P = 0.20) with low heterogeneity (I2 = 13.3%, P = 0.32). For the secondary outcomes, pioglitazone did not substantially affect the pooled estimates of these endpoints except late loss (P = 0.01) and TVR (P = 0.04).The limited evidence indicates that pioglitazone does not demonstrate markedly beneficial effect in patients subjected to coronary DES implantation. However, the results should be interpreted with care given the small sample size. Further large-scale RCTs are needed.